ANALISIS PRAKTIK AKAD IJARAH MUNTAHIYAH BI AL-TAMLIK DALAM LEMBAGA PEMBIAYAAN SYARIAH DI INDONESIA - Rodliyah, Nunung; Famulia, Ledy; K, Ade Oktariatas (Journal of Islamic Law Studies, 2021)
Awareness of muslims as a people the majority of the population to behave in islamic is one reason the development of syariah banking in indonesia. Significantly, in defending its existence, islamic banking industry continued to innovation for shariah products, in accordance with society development one of the Islamic banking products is ijarah muntahiyah bi al-tamlik. The ijarah muntahiyah bi al-tamlik contract is one of the relatively new contracts, because it combines several types of contracts in a contract. For some of these reasons, the authors are interested in discussing more about the legal aspects of the ijarah muntahiyah bi al-tamlik and how they are practiced in Islamic finance institutions. The research method used is a qualitative method with a type of normative juridical research. The conclusion obtained is that the contract of the ijarah muntahiyah bi al-tamlik which is a lease agreement that ends with ownership is permissible in Islam. This was confirmed by the DSN-MUI fatwa No. 27 / DSN-MUI / III / 2002 concerning the Ijarah muntahiyah bi al-tamlik. Even in practice, there have been several rules from Bank Indonesia and the Financial Services Authority which specifically regulate the implementation of the ijarah muntahiyah bi al-tamlik contract.